Distribution Pattern of Genus Taraxacum in the Nepalese Himalayas - Luintel, Sanjeev (Himalayan Biodiversity, 2020)
The flowering plant diversity in Nepal is very rich with wide range of distribution due to overlap of different phytogeographical regions. In this study, we accounted the distribution pattern of genus Taraxacum belonging to the family Asteraceae. We included 14 species of Nepalese species which have wide range of altitudinal distribution i.e. from tropical region of Terai (720 m asl) to high Himalayas (4850 m asl) and east to west horizontal distribution with most of the species dominant in the central region of Nepal. Most of the species disappear or die during the dry winter season and their flowering starts by the starting of the Monsoon. These species within the genus have extended flowering period which is not strictly constrained by the monsoon. Taraxacum species richness increases along the elevation gradient from west to east across Nepal, in relation to the increased intensity of the monsoon.